The art of colour the history of art in 39 pigments - Grovier, Kelly 1968- (Yale University Press, 2023)
"A captivating new history of art told through the storied biographies of colors and pigments. In this refreshing approach to the history of color, Kelly Grovier takes readers on an exciting search for the intriguing and unusual. In Grovier's telling, a color's connotations are never fixed but are endlessly evolving. Knowledge of a pigment and its history can unlock meaning in the works that feature it. Grovier employs the term "artymology" to suggest that color is a linguistic device, where pigments stand in for syllables in art's language. Color is the site of invigorating conflict--a battleground where past and present, influence and originality, and superstition and science merge into meanings that complicate and intensify our appreciation of a given work. How might it change our understanding of a well-known masterpiece like Vincent van Gogh's Starry Night to know that the intense yellow moon in that painting was sculpted from clumps of dehydrated urine from cows that were fed nothing but mango leaves? Or that the cobalt blue pigment in Van Gogh's sky shares a material bloodline with the glaze of Ming Dynasty porcelain? Consisting of ten chapters, each presenting a biography of a family of colors, this volume mines a rich vein of pigmentation from prehistoric cave painting to art of the present day. The book also includes beautifully designed features exploring important milestones in the history of color theory from the Enlightenment to the twentieth century."--Publisher's website
Keywords: Pigments / History; Colors / History; Color in art / History; ART / History / General